Development of KIT-Based Learning Media to Improve Science Learning Outcomes on Light and Optics - Maiyanti, Aziza Anggi; Malika, Nia Ellia; Rahmawati, Anis Nabil; Yusal, Yulianti; Moryati, Yulisna (Proceeding International Conference on Education, 2025)
This study aims to develop simple, effective, and feasible KIT-based learning media to improve science learning outcomes in light and optics in grade 8. The media was developed using the Research and Development (R&D) model. The media feasibility test showed that the practical KIT on the properties of light was feasible for use, with a percentage of 72.5%. The media was also highly rated by teachers and students based on the responses obtained, with 85.5% and 88.96% respectively categorizing it as highly suitable. The effectiveness of the KIT media was tested by comparing the learning outcomes of students who used the KIT media with those who used conventional methods. The hypothesis test results showed that the use of KIT media in learning could improve student learning outcomes (t-count < t-table or 0.000 < 2.039). This indicates that the KIT media can be an effective alternative in enhancing students' understanding of light and optics. This study contributes to the development of simple KIT-based learning media that can be used as an additional option in science learning. This media is expected to increase students' interest and learning outcomes, as well as help teachers deliver light and optics material in a more interesting and interactive way. The development of KIT-based learning media opens up opportunities for further research into the effectiveness of KIT media in other science subjects and at various levels of education.